Quantum aspects in text perception - Kuchumova, G.Zh.; Toleubayeva, A.M.; Beisenova, Zh.S. (Mediterranean Journal of Social Sciences Vol. 5 No. 4, 573 - 577, 2014)
Text is difficult to study because it is a psychological phenomenon, one that intimately associated with other aspects of psychological structure. That is, the purpose of this article is to shed some light on the nature and structure of text taking into consideration recent achievements of cognitive science, information theory and quantum linguistics. Consequently, the given paper attempts to present as clearly and simply as possible the fundamental insights about titles of literary texts because the study of titles might provide the key to understanding the author’s intention encoded in text. In this paper we shall explore some properties of the text perception aiming at deciphering the author’s intention. In particular, we intend to examine the cognitive nature of two kinds of relations named prospection and retrospection between such compulsory components of any text (the possibility of exceptions is not excluded) as its title and body. The research carried out with the help of such methods as linguistic analysis, contextual analysis, perceptive analysis, and method of quantification resulted in conclusion that title of text plays a significant role in text perception and interpretation processes performing the function of ‘a generator’ that facilitates text quantification process. Due to text title the reader concentrates on key words, expressions, images carrying meaningful information for text understanding. The given findings can be certainly employed in creation of computer programs aimed at automatic deciphering core information in texts or literary text translation practice.
Keywords: text perception, quanta, quantum linguistics, prospection, retrospection